Gene Expression during BTEX Biodegradation by a Microbial Consortium Acclimatized to Unleaded Gasoline and a Pseudomonas putida Strain (HM346961) Isolated from It - Jesús A. Morlett Chávez; Jorge Á. Ascacio Martínez; William E. Haskins; Hugo A. Barrera Saldaña; Karim Acuña Askar (Polish Journal of Microbiology, 2017)
Pseudomonas putida strain (HM346961) was isolated from a consortium of bacteria acclimatized to unleaded gasoline-contaminated water. The consortium can efficiently remove benzene, toluene, ethylbenzene and xylene (BTEX) isomers, and a similar capability was observed with the P. putida strain. Proteome of this strain showed certain similarities with that of other strains exposed to the hydrocarbon compounds. Furthermore, the toluene di-oxygenase (tod) gene was up-regulated in P. putida strain when exposed to toluene, ethylbenzene, xylene, and BTEX. In contrast, the tod gene of P. putida F1 (ATCC 700007) was up-regulated only in the presence of toluene and BTEX. Several differences in the nucleotide and protein sequences of these two tod genes were observed. This suggests that tod up-regulation in P. putida strain may partially explain their great capacity to remove aromatic compounds, relative to P. putida F1. Therefore, new tod and P. putida strain are promising for various environmental applications.